Treatment of Esophageal-Pleural Fistula After Diverticulectomy Using Transluminal Vacuum Therapy in a Patient with HIV Infection - M. A. Panasyuk; G. Yu. Aldaranov; V. N. Makhutov; E. G. Grigoriev (Неотложная медицинская помощь)
Abstract A clinical observation of the successful treatment of an HIV-infected patient with esophageal-pleural fistula and pleural empyema after diverticulectomy is presented, where the key tactical decision was the use of transluminal vacuum therapy together with adequate drainage of the pleural cavity and correct drug therapy. When analyzing the available literature, no publications concerning the treatment of HIV-infected patients with the discussed esophageal pathology were found.Aim of study To discuss the Results of treatment of postoperative esophageal-pleural fistula using transluminal vacuum therapy in a patient with HIV infection.